Effects of Cu and Zn contamination on soil biological indicators of environmental quality - WANG Xiu-li; XU Jian-ming; XIE Zheng-miao; YAO Huai-ying; SHI Wei-yong (浙江大学学报. 农业与生命科学版)
Some important biological parameters, namely, microbial biomass carbon, microbial biomass nitrogen, microbial quotient, metabolic quotient and soil enzyme activity in a heavy metal contaminated soil around a Copper (Cu)-Zinc (Zn) smelter in Fuyang city of Zhejiang Province were measured to assess soil quality. The result showed that the main heavy metal elements found in the polluted area were Cu and Zn which inhibited the soil phosphatase and catalase activities to different extent. A significant positive correlation was shown to exist between available Cu, Zn content and soil metabolic quotient whereas a negative correlation between available Cu, Zn content and microbial biomass carbon, microbial biomass nitrogen as well as microbial quotient.